Bioinformatics tools in conservation biology - Shivji, Mahmood; Richards, Vincent (Henry Stewart Talks, 2007)
Conservation biology and genetics, Working with DNA sequences, Statistical tools for measuring genetic diversity, Genetic diversity and conservation: case studies, Phylogenetic tools for assessing genetic diversity, Phylogenetics and conservation: case studies, Measuring genetic distance, DNA forensics and applications to conservation
Reviewed at 2017/04/20